Economic Sustainability and Social Equality in the Technological Era: Proceedings of the 3rd International Conference on Humanities and Social Sciences (ICHSOS 2023), 30–31 August 2023, Malang, Indonesia - Dwi Irawan; Agung Prasetyo Nugroho Wicaksono; Aviani Widyastuti; Rizki Febriani; Ali Roziqin (Routledge, 2025)
This book is a comprehensive compilation of academic papers and presentations delivered at the conference. It brings together research from various disciplines within the humanities and social sciences, such as cultural studies, sociology, psychology, education, literature, and history. It meticulously covers several critical areas of study, reflecting the diverse and interdisciplinary nature of the conference. In the realm of post-pandemic economic development, it explores strategies for economic recovery and resilience, highlighting the role of finance and social capital in rebuilding economies. Technology and sustainable cities are examined through case studies and theoretical frameworks that discuss smart city initiatives, technological integration, and sustainability practices. The section on economic development, accountability, and finance risk delves into methods for ensuring transparency and managing financial uncertainties in a globalized economy. Social and environmental policies and planning are addressed with a focus on creating equitable and sustainable communities. This text will be valuable to academics, researchers, and students in the fields of humanities and social sciences. The Open Access version of this book, available at http://www.taylorfrancis.com, has been made available under a Creative Commons [Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND)] 4.0 license.
Keywords: 300; Social Science; Economic Sustainability; Social Equality; Social Class